Hydrogen peroxide-independent generation of superoxide by plant peroxidase: hypotheses and supportive data employing ferrous ion as a model stimulus - Kimura, Makoto; Umemoto, Yosuke; Kawano, Tomonori (Frontiers in Plant Science, 2014)
When plants are threaten by microbial attacks or treated with elicitors, alkalization of extracellular space is often induced and thus pH-dependent extracellular peroxidase-mediated oxidative burst reportedly takes place, especially at the site of microbial challenge. However, direct stimulus involved in activation of peroxidase-catalyzed oxidative burst has not been identified to date. Here, we would like to propose a likely role for free ferrous ion in reduction of ferric native peroxidase into ferrous enzyme intermediate which readily produces superoxide anion via mechanism involving Compound III, especially under alkaline condition, thus, possibly contributing to the plant defense mechanism. Through spectroscopic and chemiluminescence analyses of reactions catalysed by horseradish peroxidase, the present study proposed that plant peroxidase-catalysed production of superoxide anion can be stimulated in the absence of conventional peroxidase substrates but in the presence of free ferrous ion.